Cropland Amendment with Beef Cattle Manure Minimally Affects Antimicrobial Resistance. Issue 6 (1st November 2019) - Miller, Eric; Spiehs, Mindy; Arthur, Terrance M.; Woodbury, Bryan; Cortus, Erin; Chatterjee, Amitava; Rahman, Shafiqur; Schmidt, John W.
Abstract : Concerns exist that beef cattle manure amendment may increase antimicrobial resistance (AMR) in cropland soils and persist over time, potentially increasing food‐animal and human exposure via feed and produce. Manure and soil contain many types of antibiotic‐resistant bacteria. However, zoonotic pathogens and fecal indicators are most directly linked to human disease and environmental surveillance efforts. We measured the levels of eight antimicrobial resistant zoonotic pathogens and fecal indicators at experimental farms at three locations: Nebraska (silt loam), North Dakota (silty clay), and South Dakota (silty clay loam). Each location had four treatments: beef cattle manure, beef cattle manure with corn stover bedding, inorganic fertilizer, and unamended control. Tetracycline‐resistant (TET r ), nalidixic‐acid resistant, and third‐generation cephalosporin‐resistant (3GC r ) Salmonella enterica were not detected in any cropland samples. Treatments did not significantly affect cropland levels of TET r Escherichia coli, trimethoprim‐sulfamethoxazole‐resistant E. coli, 3GC r E. coli, TET r Enterococcus spp., or erythromycin‐resistant Enterococcus. Additionally, levels of 10 antimicrobial resistance genes (ARGs) were assessed in all soil samples. Except for erm (B) and tet (M) at Nebraska, ARG increases after manure application dissipated before planting occurred. Treatment did not affect the following ARGs: aac (6′)‐ Ie ‐ aph (2′′)‐ Ia, aadA1, bla CMY‐2, bla CTX‐M, mecA, tet (A), and tet (B). The replicated experimental design, quantification data, and paired genotypic and phenotypic information collected for this study can be used to inform risk assessment models. The common US Upper Midwest practice of land applying beef cattle manure in fall does not result in significantly higher levels of the AMR tested in spring cropland soils. Core Ideas: Beef manure amendment did not affect soil levels of resistant pathogens and indicator bacteria levels. Beef manure amendment minimally affected antimicrobial resistance gene levels. Sample occasion had a larger effect than amendment on soil antimicrobial resistance levels.